Proteome solubility is differentially reshaped by thermal stress and regulators of ubiquitination - Hunt, Liam C.; Stephan, Anna; Poudel, Suresh; Yu, Kaiwen; Kavdia, Kanisha; Pagala, Vishwajeeth R.; Wang, Wei; Fu, Yingxue; Wang, Yong-Dong; Wang, Xusheng; Graca, Flavia A.; Alford, Daniel; et al. (The Journal of biological chemistry, 2025)
The ubiquitin-proteasome system maintains proteostasis by degrading proteins that unfold and become insoluble upon stress. Some proteins have high insolubility in normal conditions because of their structure, subcellular localization, and interactions but it remains incompletely understood how the ubiquitin-proteasome system regulates them. Here, we utilized mass spectrometry to profile heat-induced solubility changes (insolubilome) and associated post-translational modifications in human cells (http://thermal-stress-insolubilome.stjude.org). We find that the solubility of several protein categories is oppositely modulated by thermal stress. Some proteins become more soluble upon heat shock, whereas others, including several ubiquitin-conjugating enzymes, become more insoluble. By analyzing the changes in protein abundance induced by RNAi for E2 ubiquitin-conjugating enzymes, we identify E2-specific biases in targeting proteins with higher-than-average insolubility. Analysis of the E3 ubiquitin ligase HUWE1, which was previously found to detect proteins with exposed hydrophobic residues, indicates that siHUWE1-downregulated proteins have higher-than-average insolubility, suggesting that HUWE1 stabilizes subsets of insoluble proteins. Altogether, this study identifies components of the ubiquitination cascade that control and remodel the solubility of the human proteome.